Linear sweep voltammetry with non-triangular waveforms: New opportunities in electroanalysis - Uchida, Y; Kätelhön, E; Compton, R (Elsevier, 2018)
The voltammetry of two simultaneous electrochemically reversible reactions with different formal potentials is investigated at a macroelectrode for a conventional linear potential waveform and a herein newly proposed semi-circular potential waveform, which, at the midpoint of the potential window shows an instantaneous infinite scan rate and relatively very slow scan rates in other areas of the wave. We show that the method increases the sensitivity of detection of individual species by greatly amplifying the peak current of one species while suppressing the interference with the other species and is thus ideal for analytical applications.